The leadership knowledge among school principals on teacher's work discipline - Ismail, Mohd Zukifli; Md Rami, Ahmad Aizuddin; Muhamad, Mohd Mokhtar; Abdul Aziz, Nor Azni (Microthink Institute, 2023)
This study was to examine the principal's leadership level of understanding on the teacher's work discipline in one school at Federal Territory of Labuan, Malaysia. A total of 131 people were included in the sample, which included all teachers in one school at Federal Territory of Labuan, Malaysia. A series of questionnaires adapted from prior research that cover the scope of this investigation, as well as survey questions generated based on operational definitions and literature reviews, were employed in this study. The most common approaches to analyzing the research objective are descriptive analysis and factor analysis. The results showed that there is a significant relationship between the level of knowledge of the principal's leadership and the teacher's discipline on demography. The implications of this study are to identify the level of knowledge of teachers regarding the ethics of the teaching profession and the discipline of teachers working within the organization. This will help the relevant parties in organizing each mechanism to further enhance the knowledge level of the principal's leadership in the profession. This study is still relevant today and will be carried out in the future with increasing issues such as integrity and value in the teaching profession.